Centrifuge study on the use of protective walls to reduce tunnelling-induced damage of buildings. (September 2021) - Song, Geyang; Marshall, Alec M.
Highlights: Effect of protective walls on reducing the impact of tunnelling on piled structures. Protective walls can reduce the tunnelling induced ground movements on the retained side. Protective wall could reduce pile settlement and structural distortions. The impact of the protective walls on pile shaft resistance development. Abstract: Tunnel excavation in urban areas causes ground movements that could damage existing nearby piled structures. In practice, to protect structures from tunnelling-induced damage, a stiff protective wall can be constructed between the tunnel and the adjacent piled structure. In this paper, results from four hybrid geotechnical centrifuge tests (where data are coupled between the centrifuge and numerical models) are used to quantify the effect of protective walls on reducing the impact of tunnelling on an adjacent framed building with four piles. Two protective walls with different embedded depths are considered: a 'shallow' wall with its toe at the tunnel axis depth and a 'deep' wall with its toe below the tunnel invert. Compared to the 'no-wall' case, the 'deep' protective wall is shown to significantly reduce uneven pile settlements, structural distortions, and load transfer (through the building) between piles; the 'shallow' wall is shown to have little benefit. Data from the instrumented walls and piles are used to explain the dominant mechanisms at play and investigate how the load is redistributed within the piles.